Foraging strategies and spatial-temporal partitioning by brown hyenas (Hyaena brunnea, Thunberg 1820) around a coastal food source: implications for conservation and ecotourism in the TsauǁKhaeb National Park, Namibia - Somers, Michael J. (University of Pretoria, 2025)
Thesis (PhD (Wildlife Management))--University of Pretoria, 2024.